1976
DOI: 10.7164/antibiotics.29.292
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of antibiotics. I. Acylation of chloramphenicol by spores of Streptomyces griseus isolated from the egyptian soil.

Abstract: Incubation of spores, washed mycelium or whole cultures of a Streptomyces sp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The singlet at δ 6.22 (−CHCl 2 ) and the complex resonance at δ 4.46 (m, H −2′) were identical to that of chloramphenicol. [38, 39] The DEPT experiment indicated the presence of one carbonyl group, suggesting compound 1 was a chloramphenicol ester. The acyl group was determined to be isobutyrate based on the molecular formula of compound 1 differing from that of chloramphenicol by C 4 H 7 O and the 1 H NMR doublet at δ 1.17 integrated to six protons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The singlet at δ 6.22 (−CHCl 2 ) and the complex resonance at δ 4.46 (m, H −2′) were identical to that of chloramphenicol. [38, 39] The DEPT experiment indicated the presence of one carbonyl group, suggesting compound 1 was a chloramphenicol ester. The acyl group was determined to be isobutyrate based on the molecular formula of compound 1 differing from that of chloramphenicol by C 4 H 7 O and the 1 H NMR doublet at δ 1.17 integrated to six protons.…”
Section: Resultsmentioning
confidence: 99%
“…The acyl group was determined to be isobutyrate based on the molecular formula of compound 1 differing from that of chloramphenicol by C 4 H 7 O and the 1 H NMR doublet at δ 1.17 integrated to six protons. The location of the isobutyrate group was determined at C-3′ hydroxyl based on the chemical shift of H-3′ at δ 3.5 in chloramphenicol has shifted to 4.30 and 4.42 ppm (Additional file 1: Table S1) [38, 39]. HRMS analysis gave a [M + Na] + of 415.0440 ( calc .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] A few papers reported that the synthesis of the drug derivatives was catalyzed by enzymes. El-Kersh [13] reported the acyl derivatives of chlormaphenicol were obtained through biological catalysis. Ottolina [14] reported that the regioselective esterification of chloramphenicol and its synthetic analogue thiamphenicol has been achieved by the action of lipases in acetone.…”
Section: Introductionmentioning
confidence: 99%
“…Although this theory does not require the corresponding genes to be permanently plasmid-linked in their streptomycete hosts, the normal carriage of such genes on plasmids might have favoured their dissemination from such hosts to other bacteria. Of the antibiotic-inactivating enzymes coded by eubacterial plasmids, those catalysing acetylation or phosphorylation of aminoglycosides or acetylation of chloramphenicol are found in various streptomycetes (Benveniste & Davies, I 973 ; El- Kersch & Plourde, 1976a;Shaw & Hopwood, 1976;Nakano et al, 1977). However, nothing appears to be known in these organisms about the genetic determination of these enzymes because they have not been studied in genetically characterized strains.…”
mentioning
confidence: 99%